Daun Cincau Hijau (Premna Oblongifolia) Has the Potential to Improve Spermatozoa Quality in Hyperglycemic White Rats (Rattus Norvegicus) - Etty Widayanti; Aan Royhan; Annisa Nur Azzahra Kananta; Annisa Azzahra (Eduvest - Journal of Universal Studies, 2026)
Diabetes mellitus is a health problem that has a wide impact on various organs, including the male reproductive system. Chronic hyperglycemia can increase oxidative stress and deteriorate the morphological quality of spermatozoa. The leaves of the green grasshopper (Premna oblongifolia) contain flavonoids and antioxidants that have the potential to suppress oxidative stress and repair histological damage caused by hyperglycemia. This study aims to assess the effect of green grasshopper leaf extract on blood glucose levels and spermatozoa quality by evaluating the Johnsen score and spermatozoa morphology in hyperglycemic mice. The study used an experimental design with a post-test-only control group approach. A total of twenty-four male mice were randomly divided into four groups: normal control, negative control, and two treatment groups that received green grasshopper leaf extract at doses of 200 and 400 mg per kg of body weight. Diabetes was induced using streptozotocin, while the green grasshopper leaf extract was obtained by the maceration method and administered orally for fourteen days. The results showed that a dose of 400 mg per kg of body weight significantly reduced blood glucose levels compared to the negative control. In addition, the high-dose treatment group showed a near-normal Johnsen score and a decrease in the number of abnormal spermatozoa. These findings indicate that green grasshopper leaf extract has potential as a phytotherapeutic agent that not only lowers blood glucose levels but also improves the reproductive quality of males impaired by diabetes mellitus.